Mapping Polyamide–DNA Interactions in Human Cells Reveals a New Design Strategy for Effective Targeting of Genomic Sites1. (25th July 2014) - Erwin, Graham S.; Bhimsaria, Devesh; Eguchi, Asuka; Ansari, Aseem Z.
Abstract Targeting the genome with sequence‐specific synthetic molecules is a major goal at the interface of chemistry, biology, and personalized medicine. Pyrrole/imidazole‐based polyamides can be rationally designed to target specific DNA sequences with exquisite precision in vitro; yet, the biological outcomes are often difficult to interpret using current models of binding energetics. To directly identify the binding sites of polyamides across the genome, we designed, synthesized, and tested polyamide derivatives that enabled covalent crosslinking and localization of polyamide–DNA interaction sites in live human cells. Bioinformatic analysis of the data reveals that clustered binding sites, spanning a broad range of affinities, best predict occupancy in cells. In contrast to the prevailing paradigm of targeting single high‐affinity sites, our results point to a new design principle to deploy polyamides and perhaps other synthetic molecules to effectively target desired genomic sites in vivo.